2007
DOI: 10.2105/ajph.2005.081117
|View full text |Cite
|
Sign up to set email alerts
|

The Creation of Industry Front Groups: The Tobacco Industry and “Get Government Off Our Back”

Abstract: We investigated how industries use front groups to combat public health measures by analyzing tobacco industry documents, contemporaneous media reports, journal articles, and press releases regarding "Get Government Off Our Back," a coalition created by the tobacco industry. RJ Reynolds created Get Government Off Our Back in 1994 to fight federal regulation of tobacco. By keeping its involvement secret, RJ Reynolds was able to draw public and legislative support and to avoid the tobacco industry reputation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 32 publications
0
70
1
Order By: Relevance
“…Much like tobacco companies, the soda industry formed local community coalitions who spoke for them in the news (Apollonio & Bero, 2007a, 2007bBrownell & Warner, 2009;Samuels & Glantz, 1991;Yanamadala et al, 2012). Unlike in earlier analyses of soda tax campaigns, however, we found that the soda industry itself was largely absent from news coverage of the soda taxes.…”
Section: Discussioncontrasting
confidence: 86%
“…Much like tobacco companies, the soda industry formed local community coalitions who spoke for them in the news (Apollonio & Bero, 2007a, 2007bBrownell & Warner, 2009;Samuels & Glantz, 1991;Yanamadala et al, 2012). Unlike in earlier analyses of soda tax campaigns, however, we found that the soda industry itself was largely absent from news coverage of the soda taxes.…”
Section: Discussioncontrasting
confidence: 86%
“…should be asked about their sponsors 17 and that media investigation of sponsors has frequently limited the effectiveness of front groups. 18 While past TID campaigns have successfully used messages about tobacco industry manipulation and marketing practices, novel messages are periodically required, 6 with information about the use of front groups within the tobacco industry one possibility.…”
Section: Discussionmentioning
confidence: 99%
“…McNutt and Boland (2007) provide an overview of the astroturfing phenomenon and discuss its implications for nonprofit organizations. Apollonio and Bero (2007) and Tsoukalas and Glantz (2003) describe the astroturfing activities of the tobacco industry in terms of processes, success, and implications for the public. Lyon and Maxwell (2004) take a slightly different definition of astroturfing (i.e., a strategy ''in which a firm that knows the state of the world subsidizes the lobbying activities of a group with similar views'' (p. 594)) and, using analytical modeling, show that a law requiring disclosure of astroturfing expenditures would reduce the effectiveness of astroturfing, which would be desirable by public decision-makers.…”
Section: Grassroots or Astroturf?mentioning
confidence: 99%